2012
DOI: 10.1111/j.1742-4658.2012.08680.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptides that inhibit HIV‐1 integrase by blocking its protein–protein interactions

Abstract: HIV‐1 integrase (IN) is one of the key enzymes in the viral replication cycle. It mediates the integration of viral cDNA into the host cell genome. IN activity requires interactions with several viral and cellular proteins, as well as IN oligomerization. Inhibition of IN is an important target for the development of anti‐HIV therapies, but there is currently only one anti‐HIV drug used in the clinic that targets IN. Several other small‐molecule anti‐IN drug leads are either undergoing clinical trials or in ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 113 publications
(159 reference statements)
0
28
0
1
Order By: Relevance
“…H45 D Wichner et al drugs that target different stages of the viral replication cycle, a procedure that overcomes the development of resistance in the virus due to its high mutation rate. 27 HIV integrase is one of the key enzymes in the virus replication cycle as it is responsible for the integration of the reverse transcribed viral complementary DNA (cDNA) into the host cell genome. 28 Raltegravir is the first FDA clinically approved HIV integrase inhibitor used to treat both HIV-1 infections in treatment-experienced adult patients who have evidence of viral replication and HIV-1 strains resistant to multiple antiretroviral agents.…”
Section: Discussionmentioning
confidence: 99%
“…H45 D Wichner et al drugs that target different stages of the viral replication cycle, a procedure that overcomes the development of resistance in the virus due to its high mutation rate. 27 HIV integrase is one of the key enzymes in the virus replication cycle as it is responsible for the integration of the reverse transcribed viral complementary DNA (cDNA) into the host cell genome. 28 Raltegravir is the first FDA clinically approved HIV integrase inhibitor used to treat both HIV-1 infections in treatment-experienced adult patients who have evidence of viral replication and HIV-1 strains resistant to multiple antiretroviral agents.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, IN is no exception with the CCD–CCD dimer interface alone comprising ~1500 Å 2 , which significantly exceeds the potential of a small molecule binding site. The majority of work to interfere with IN dimerization has focused on developing various peptides [reviewed in (Maes et al 2012)]. Most notably, peptides derived from the CCD α1 and α5 helixes, which mediate CCD–CCD interactions, have been able to disrupt IN dimerization (Maroun et al 2001).…”
Section: Small Molecules Promote Aberrant Higher Order Hiv-1 Integmentioning
confidence: 99%
“…Dolutegravir is an antiviral drug which is structurally diverse and can bind to various catalytic domains of various proteins [34]. In a study conducted in 2012, this drug was docked with HIV-I integrase and it was reported that it can cause inhibition [35], which is an attractive target for novel anti-AIDS agents. In another study, it was observed that this drug can form different sorts of interactions with Try99, Ala98, Glu170, Thr174, Gln168, and His171 [36].…”
Section: Discussionmentioning
confidence: 99%